Penerapan Algoritma DNA dalam Membangkitkan Kunci pada Algoritma Elgamal - Khoiroh, Ihda Umdatul; Turmudi, Turmudi; Sujarwo, Imam (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2024)
The security of secret messages is an important aspect that must be preserved to prevent public knowledge of the information contained within. One way to secure messages is by utilizing the assistance of cryptography. By employing algorithms found in cryptography, messages are disguised in a manner that makes them difficult to decipher. In this research, the DNA algorithm is used in the key generation process of the Elgamal algorithm. The objective of this research is to enhance the security of plaintext by modifying the key generation process, thereby making it difficult for others to crack the key. The result of this research is the encrypted private key x using the DNA algorithm and the public key g, which is a primitive root of the selected prime number that is further encrypted using the DNA algorithm, resulting in a new public key. Consequently, prior to encrypting the plaintext, decryption of the public key must be performed first.